EVALUASI EFEKTIVITAS BRAND AWARENESS, CONTENT MARKETING, VALUE, DAN PRICING TERHADAP KEPUTUSAN PEMBELIAN PRODUK B2C SKINTIFIC PADA PLATFORM TIKTOK (STUDI KASUS PADA MAHASISWA UNIVERSITAS MURNI TEGUH) - Winata, Angellyna Surya; Sirait, Sarida; Simarmata, Hengki M. P. Simarmata; Nathania, Beatrice; Berlien, Richard (Politeknik Bisnis Indonesia, 2024)
This research aims to determine the significance of the effectiveness of Brand Awareness, Content Marketing, Value, and Pricing on the Purchase Decision of B2C Skintific products on the TikTok platform. This research shows that the decline in Skintific product sales is caused by the high and uneconomical product price, particularly for students at Universitas Murni Teguh. This is an associative research with a quantitative approach. The variables studied include Brand Awareness, Content Marketing, Value, Pricing, and Purchase Decision. The sampling technique used in this research is non-probability sampling with purposive sampling method, measured using the Slovin formula, with a sample size of 270 respondents. The data used is primary data collected through questionnaires. The data analysis technique includes several stages. First, instrument testing is conducted to measure validity and reliability. Next, classical assumption testing is performed, including normality test, multicollinearity test, and heteroscedasticity test. Finally, analysis is continued with multiple linear regression and hypothesis testing, including t-test, F-test, and coefficient of determination test. The results show that Brand Awareness, Content Marketing, Value, and Pricing have a positive and significant effect on the Purchase Decision of B2C Skintific products on TikTok. Partially, the tvalues for Brand Awareness (4,746), Content Marketing (4,974), Value (9,757), and Pricing (5,721) are each greater than the ttable (1,969) with a significance level < 0,05. Additionally, simultaneous analysis shows that the Fvalue (103,955) is greater than the Ftable (2,41), indicating that all four variables together have a positive and significant effect on Purchase Decisions. Based on the coefficient of determination test, the Adjusted R Square value is 0,605, meaning that the variables Brand Awareness, Content Marketing, Value, and Pricing account for 60,5% of the effect on Purchase Decision, while the remaining 39,5% is influenced by other variables not discussed in this research.